Association Between Left Ventricle Diastolic Dysfunction and Unfavorable Prognostic Markers in Patients with Aortic Insufficiency - Roscani, Meliza Goi; Duarte, Juliana Da Cunha; Augusto, Gustavo Nicolodi; De Moraes Salgueiro, Thaysa Rodrigues; Meireles, Mariana N.; Gobbi, Juliana I. F. [UNESP]; Okoshi, Katashi; Hueb, Joao Carlos (Premchand Shantidevi Research Foundation, 2017)
Introduction: The presence of symptoms, systolic dysfunction and Left Ventricle (LV) dilation are considered unfavourable prognostic markers in Aortic Valve Insufficiency (AVI). The role of diastolic dysfunction, which is considered unfavourable outcome marker in cardiac pathologies, is not well established in AVI. Aim: To evaluate if the presence of diastolic dysfunction may be associated with unfavourable prognostic markers in AVI patients. Materials and Methods: A cross-sectional prospective study was performed on 22 patients with moderate or severe AVI. They underwent clinical evaluation and transthoracic echocardiography. Associations between clinical, epidemio-logical and echocardiographic were evaluated by Student t-test for normally distributed variables or Mann-Whitney test for non-normal distribution. Comparison between proportions was performed by Chi-square test. Results: There was an association between increased LV filling pressure, assessed by E' and E/E' of Mitral Tissue Doppler, and impaired LV systolic function, respectively: R = 0.563, R-2 = 0.281; p = 0.008 and R = 0.639, R-2 = 0.378; p = 0.002. The LV indexed mass also was inversely associated with the LV ejection fraction (R = 0.62, R2 = 0.35 and p = 0.003). Conclusion: There was an association of LV diastolic dysfunction and ventricular hypertrophy with impaired left ventricle systolic function. Increased LV filling pressure and LV indexed mass should be considered in the management of AVI patients.
Keywords: Echocardiogram; Left ventricle filling pressure; Myocardial eccentric hypertrophy; Volume overload